Anatomical characterization of the digestive system of the pufferfish (Chilomycterus spinosus spinosus) - Thiago Scremin Boscolo Pereira; André Del Arco; Patrícia Hoffmann; Vanessa Belentani Marques (Acta Scientiarum. Biological Sciences, 2019)
Descriptive studies of the fish digestive system are fundamental because they provide information on the biology of the species. Thus, the objective of this study was to morphologically describe the digestive system of the pufferfish, Chilomycterus spinosus spinosus. For this, adult specimens of pufferfish (n = 10) of both sexes were used. The animals were fixed with 10% aqueous formaldehyde solution, dissected, analyzed descriptively and photographed. The results demonstrate that the pufferfish has a morphologically modified digestive system, which is adapted to the defense behavior. This species presents a pouch-shaped diverticulum, that is called abdominal pouch, which allows the expansion of the celomatic cavity and the temporary storage of food. Although it is used to store food, macroscopically the abdominal pouch does not show gastric folds. However, this absence is compensated by a small intestine containing innumerable villi.